Serum plasminogen activator inhibitor-1 levels in patients with major depressive disorder vs. healthy controls: a systematic review and meta-analysis - Mohamed Elsayed; Khaled A. Mohamed; Khaled T. Dardeer; Dalia K. Zaafar; Soha Osama Hassanin; Ramy Abdelnaby; Carlos Schönfeldt-Lecuona (Trends in Psychiatry and Psychotherapy, 2023)
Abstract Introduction Major depressive disorder (MDD) is a severe mental health condition that affects millions of people worldwide. Etiologically, several factors may play a role in its development. Previous studies have reported elevated plasminogen activator inhibitor-1 (PAI-1) levels in patients with depression, suggesting that PAI-1 levels might be linked to the etiology of MDD. Methods We systematically searched the following online databases: MEDLINE, Scopus, and Web of Science up to September 10, 2020, to identify studies in which PAI-1 levels were reported in subjects with MDD. Subsequently we used RevMan 5.3 to perform a meta-analysis of data extracted from the included studies using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and PICO criteria for the search and analysis. Results Six studies that reported mean ± standard deviation (SD) were included in the analysis, with a total of 507 MDD patients and 3,453 controls. The overall standardized mean difference (SMD) was 0.27 (95% confidence interval [95% CI] 0.01-0.53). PAI-1 serum levels were 0.27 SDs higher in MDD patients than in controls. The test for overall effect was significant (z = 2.04, p = 0.04). Substantial heterogeneity was detected among the studies, demonstrated by the inconsistency test (I2 = 72%) and the chi-square test (χ2 = 18.32; p = 0.003). Conclusion This systematic review and meta-analysis showed that MDD might be related to elevated PAI-1 levels. We propose larger prospective clinical studies to further investigate this clinical correlation and validate the clinical significance of these observations.